Zinc content and yield of biofortified cowpea beans - Márquez-Quiroz, César; de-la-Cruz-Lázaro, Efraín; Osorio-Osorio, Rodolfo; Sánchez-Chávez, Esteban; Huijara-Vasconcelos, José Javier; Sida-Arreola, Juan Pedro (Revista Mexicana de Ciencias Agrícolas, 2018)
Zinc (Zn) is an essential trace element for plants, animals and humans; consequently, their deficiency affects their growth and development. It is estimated that between 15 and 30% of the human population in the world exhibit Zn deficiencies. The objective was to study the effect of biofortification with Zn2+ on the mineral content and yield of cowpea beans. The experiment was developed under a completely random design in two production cycles. The Zn was applied as zinc sulphate (T1: 0 µM L-1, T2: 25 µM L-1, T3: 50 µM L-1 and T4: 100 µM L-1) and as zinc chelate (T5: 0 µM L-1, T6: 25 µM L-1, T7: 50 µM L-1 and T8: 100 µM L-1). The applications of 25 μM L-1 of ZnSO4 and 50 μM L-1 of Zn-EDTA for both production cycles were the most effective in increasing the content of this element in the bean seed cowpea, determining 1.14 and 0.93 times more zinc respectively, compared to the control. The yield, in cycle 1, was decreased by 53.8 and 20.3% by applying 50 μM L-1 of ZnSO4 and 25 μM L-1 of Zn-EDTA, respectively. The addition of 50 μM L-1 of ZnSO4 and 25 μM L-1 of Zn-EDTA, in cycle 2, increased the yield by 16.7 and 37.3%, respectively, compared to the control. The best treatments to biofortify cowpea beans were 25 μM L-1 of ZnSO4 and 50 μM L-1 of Zn-EDTA for both production cycles.